InsÄn KÄmil In The Religious Existentialism Philosophy Of Seyyed Hossein Nasr - Encung Encung; Suparman Syukur; Ilyas Supena (Jurnal Hikmatuna, 2020)
Academic investigations in this paper wants to elaborate the two concept of theistic existentialism and Sufism on human perfection (InsÄn kÄmil) of Seyyed Hossein Nasr perspective. According to Nasrâ€™s thought human is not dealing with the concept of any other creation of god like animal, thress or miniral. For human developing in the world, human being is ceated deferrently of any aspects of things. By using the comparison method analysis of ideas contained in the literature this article aims to direct the human will for actions in their life and with the method of interpreting of the hermeneutics ways of these ideas the researcher entrenched searching for sources relevant to the topic of this study. From the results of this study it was concluded that humans do not merely exist based on their material form or physical form, but humans who exist consciously of their existence are human nature according to the flows of existentialism. The human existence surely determinated by god wills and god almighty. It is different with humans who are conceived by modern sciences as experiencing disparities in understanding of humanism. So humans are often seen from a certain aspect. And this is according to the conclusion that found is caused the crisis of modernity. For this reason, measuring humanity as a creature is expected to have a large role in alleviating various crises that arise in the modern world. Humanism consciousness or human consciousness becomes an important mode of transufquration in concepting humans in the existentialism dimension.